British conservatism and trade unionism, 1945-1964 - Dorey, Peter, 1959- (Modern economic and social history series., 2009)
This book examines the a brief period between the end of the Second World War and the election of Harold Wilson's Labour government in 1964, when the Conservative Party adopted a remarkably constructive and conciliatory approach to the trade unions, dubbed 'voluntarism'. During this time the party leadership made strenuous efforts to avoid, as far as was politically possible, confrontation with, or legislation against, the trade unions, even when this incurred the wrath of some Conservative backbenchers and the Party's mass membership. Making extensive use of primary and archival sources it ex.